2022
DOI: 10.1038/s41598-022-23316-4
|View full text |Cite
|
Sign up to set email alerts
|

Survival rate and predictors of mortality among TB/HIV co-infected adult patients: retrospective cohort study

Abstract: Nowadays, Tuberculosis remains the major cause of HIV-associated mortality, which accounts for 1 out of every 5 HIV-related mortality worldwide. This study aimed to determine the survival rate and predictors of mortality among TB/HIV co-infected patients. An institution-based retrospective cohort study was undertaken on adult TB/HIV co-infected individuals between 1st February 2014 and 30th January 2022 at Mettu Karl Referral Hospital. A Cox regression model was used to identify predictors of survival time to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 45 publications
1
20
0
Order By: Relevance
“…It was observed in the multivariable analysis that hazards of mortality increased by 3.11 times (95% CI: 1.19–1.44) and 2.11 times (95% CI: 1.94–2.30) in patients with baseline CD4 count ≤50 and baseline CD4 count 51–200, respectively, as compared to those who had baseline CD4 count >200. A similar retrospective cohort study done in Oromia region, Ethiopia, on a large population of 2,775 individuals with HIV reported lower mortality (AHR = 0.719; 95% CI: 0.536–0.966) among individuals with CD4 count compared to people living with HIV with CD4 count more than 200 cells/mm 3 ( 35 ). Several studies have found a significant relationship between CD4 cell count and survival rates, implying that a low CD4 cell count is associated with an increased risk of mortality ( 36 – 38 ).…”
Section: Discussionmentioning
confidence: 93%
“…It was observed in the multivariable analysis that hazards of mortality increased by 3.11 times (95% CI: 1.19–1.44) and 2.11 times (95% CI: 1.94–2.30) in patients with baseline CD4 count ≤50 and baseline CD4 count 51–200, respectively, as compared to those who had baseline CD4 count >200. A similar retrospective cohort study done in Oromia region, Ethiopia, on a large population of 2,775 individuals with HIV reported lower mortality (AHR = 0.719; 95% CI: 0.536–0.966) among individuals with CD4 count compared to people living with HIV with CD4 count more than 200 cells/mm 3 ( 35 ). Several studies have found a significant relationship between CD4 cell count and survival rates, implying that a low CD4 cell count is associated with an increased risk of mortality ( 36 – 38 ).…”
Section: Discussionmentioning
confidence: 93%
“…Tuberculosis (TB) is a significant cause of morbidity and mortality worldwide [6], with estimates from the World Health Organization suggesting 10 million cases in 2020 alone [7]. Tragically, in the absence of adequate treatment, 5-year survival is less than 50% [8]. The geographic distribution of TB varies widely, with two-thirds of the global burden concentrated in third-world nations [9].…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have demonstrated the harmful interactions between HIV and TB, which negatively impact population health [ 4 ]. For instance, research conducted in Africa revealed that the HIV and TB epidemics are intertwined [ 5 ], while a study in Ethiopia uncovered a two-way relationship between these two diseases [ 6 ]. The detrimental and reciprocal effects of HIV and TB are evident at both individual and population levels, particularly in sub-Saharan African nations [ 7 ].…”
Section: Introductionmentioning
confidence: 99%